Graphics design work: product / Gerrard Lim - Lim, Gerrard (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Kompia House has exceptional culinary potential. However, some limitations hinder it from being recognised widely. Overcoming this challenge requires a comprehensive brand image, attractive advertisements, and immersive multimedia usage. It is expected that through robust advertising and multimedia efforts, these would help to Elevate Kompia House’s image as a renowned culinary haven, that offers an unforgettable dining experience, which surely would attract a significant influx of tourists.